2019
DOI: 10.1186/s13048-019-0597-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcome of Dienogest treatment followed by in vitro fertilization and embryo transfer in infertile women with endometriosis

Abstract: BackgroundEndometriosis is considered to be the most intractable cause of female infertility. Administering any type of treatment for endometriosis before in vitro fertilization and embryo transfer (IVF-ET) is an important strategy for improving the IVF-ET outcomes for infertile women with endometriosis. In fact, treatment with a gonadotropin-releasing hormone (GnRH) agonist just before IVF-ET has been reported to improve the clinical outcome in endometriosis patients. However, the benefit of Dienogest (DNG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 48 publications
0
41
0
3
Order By: Relevance
“…On the other hand, suppressive hormonal medication in women with endometriosis may not have bene t in terms of pregnancy rate [2]. Moreover, the administration of dienogest before the follicle aspiration in IVF in women with endometriomas did not show signi cant bene t [21]. In the view of infertility treatment, peri-operative medication should be minimized.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, suppressive hormonal medication in women with endometriosis may not have bene t in terms of pregnancy rate [2]. Moreover, the administration of dienogest before the follicle aspiration in IVF in women with endometriomas did not show signi cant bene t [21]. In the view of infertility treatment, peri-operative medication should be minimized.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, another RCT had shown that Dienogest pretreatment for patients with endometriosis before IVF was associated with a significantly lower number of oocytes retrieved and worse pregnancy outcomes [ 16 ]. Despite similarities in design, there are important differences between this trial and our study.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the use of Dienogest for control of pelvic pain due to endometriosis with beneficial and comparable effect to depot GnRHa [ 11 , 13 15 ]. However, its role in suppressing the endometriotic lesions before IVF treatment and its impact on IVF outcome is still unclear [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, suppressive hormonal medication in women with endometriosis may not have benefit in terms of pregnancy rate 2 . Moreover, the administration of dienogest before the follicle aspiration in IVF in women with endometriomas did not show significant benefit 21 . In the view of infertility treatment, peri‐operative medication should be minimized.…”
Section: Discussionmentioning
confidence: 99%